MODEL FORMAL UNTUK MEMPREDIKSI FAKTOR KEBERHASILAN UMKM DI MASA PANDEMI - Lalu Mutawalli; Saikin; Gilang Restu Imam Wahyudi (Jurnal Informatika Teknologi dan Sains, 2022)
MSMEs are one of the supports of the Indonesian economy, the impact of Covid 19 affects the decline in MSMEs in all regions of Indonesia including in Lombok. Since Pandemic Indonesia has implemented a policy of restrictions on various sectors including tourism. Restrictions impact the lack of tourist visits in Lombok it affects the growth of MSMEs in Lombok. However, some MSMEs have managed to survive even though the conditions of tourism in Lombok are still not normal. The study of the success of MSMEs that succeeded in surviving the Pandemic was needed to gain knowledge about strategies that could strengthen MSMEs. This study uses a FCA as a methodology to make an analysis. The analysis results show discounts and save money in banks, sales on medsos have the highest support of 93%, teamwork and extent capital sources of 87%, PCS, from PC, reciprocity to customers, business development training, Sales with Facebook, also business liquidity is considered sufficient at the same extent point, namely 80%, source of personal capital, product prices with market prices, CS is considered good at the same extent point, which is 73%, there is only one intent Has an extent 67% following training from the government.